Negative piezoelectric effect in an organic supramolecular ferroelectric. Issue 8 (14th May 2019) - Urbanaviciute, Indre; Meng, Xiao; Biler, Michal; Wei, Yingfen; Cornelissen, Tim D.; Bhattacharjee, Subham; Linares, Mathieu; Kemerink, Martijn
Abstract : A pronounced and tunable negative piezoelectric effect in a family of organic small-molecular ferroelectrics is demonstrated and explained. Abstract : The vast majority of ferroelectric materials demonstrate a positive piezoelectric effect. Theoretically, the negative piezoelectric coefficient d 33 could be found in certain classes of ferroelectrics, yet in practice, the number of materials showing linear longitudinal contraction with increasing applied field ( d 33 < 0) is limited to few ferroelectric polymers. Here, we measure a pronounced negative piezoelectric effect in the family of organic ferroelectric small-molecular BTAs (trialkylbenzene-1, 3, 5-tricarboxamides), which can be tuned by mesogenic tail substitution and structural disorder. While the large- and small-signal strain in highly-ordered thin-film BTA capacitor devices are dominated by intrinsic contributions and originates from piezostriction, rising disorder introduces additional extrinsic factors that boost the large-signal d 33 up to −20 pm V −1 in short-tailed molecules. Interestingly, homologues with longer mesogenic tails show a large-signal electromechanical response that is dominated by the quadratic Maxwell strain with significant mechanical softening upon polarization switching, whereas the small-signal strain remains piezostrictive. Molecular dynamics and DFT calculations both predict a positive d 33 for defect-free BTA stacks. Hence, the measured negative macroscopic d 33 is attributed to the presence of structural defects that enable the dimensional effect to dominate the piezoelectric response of BTA thin films.